Numerical Investigation of Rockburst Effect of Shock Wave on Underground Roadway - Cai-Ping Lu; Guang-Jian Liu; Hong-Yu Wang; Jun-Hua Xue (Shock and Vibration)
Using UDEC discrete element numerical simulation software and a cosine wave as vibration source, the whole process of rockburst failure and the propagation and attenuation characteristics of shock wave in coal-rock medium were investigated in detail based on the geological and mining conditions of 1111(1) working face at Zhuji coal mine. Simultaneously, by changing the thickness and strength of immediate roof overlying the mining coal seam, the whole process of rockburst failure of roadway and the attenuation properties of shock wave were understood clearly. The presented conclusions can provide some important references to prevent and control rockburst hazards triggered by shock wave interferences in deep coal mines.